Minimally Invasive Plate Osteosynthesis for Proximal Humerus Fractures: A Retrospective Study Describing Principles and Advantages of the Technique - Riccardo Luigi Alberio; Matteo Del Re; Federico Alberto Grassi (Advances in Orthopedics)
Background. The aim of this study was to evaluate the clinical and radiographic results after minimally invasive plate osteosynthesis (MIPO) for proximal humerus fractures. Potential advantages of this approach include the easier exposure of the greater tuberosity and the limited surgical dissection around the fracture site. Materials and Methods. From October 2011 to March 2016, thirty-nine patients (32 women, 7 men) with a mean age of 64.9 years (range: 48–80) were surgically treated with the MIPO technique for proximal humeral fractures. According to Neer classification, there were 12 two-part, 24 three-part, and 2 four-part fractures and 1 two-part fracture-dislocation; the AO/OTA system was also used to categorize the fractures. The Constant-Murley (CMS) and the Oxford Shoulder (OSS) Scores were used to evaluate shoulder function. Results. Thirty-four patients were available for clinical and radiographic evaluation at a mean follow-up of 31.8 months (range: 12–54 months). All fractures healed and no postoperative complications occurred. Full recovery of pretrauma activities was reported by 27 patients, while 7 patients presented mild functional limitations. The mean absolute CMS was 75.2 (range: 55–95), the mean normalized CMS was 90.5 (range: 69–107), and the mean OSS was 43.7 (range: 31–48). The only statistically significant correlation was found between the female gender and lower absolute CMS and OSS. Radiographic evaluation revealed varus malunion in 4 cases and valgus malunion in 1 case, while incomplete greater tuberosity reduction was detected in 4 cases. All malunions were related to inadequate reduction at time of surgery and not to secondary displacement. Conclusions. MIPO for proximal humeral fractures is an effective and safe surgical procedure. The limited tissue dissection allows minimizing the incidence of nonunion, avascular necrosis, and infection. The technique is not easy, requires experience to achieve mastery, and should be reserved for selected fracture patterns. In our experience, the main advantage of this approach consists in the direct access to the greater tuberosity, thus facilitating its anatomic reduction and fixation.